Fundamentals of computer architecture - Burrell, Mark (Palgrave Macmillan, 2004)
Written for students taking their first course in computer systems architecture, this is an introductory textbook that meets syllabus requirements in a simple manner without being a weighty tome. The project is based around the simulation of a typical simple microprocessor so that students gain an understanding of the fundamental concepts of computer architecture on which they can build to understand the more advanced facilities and techniques employed by modern day microprocessors. Each chapter includes a worked exercise, end of chapter exercises and definitions of key words in the margins. The book comes with a CD-ROM which includes JASPer software and the "Digital Works" package, and is accompanied by a dedicated lecturer and student web site.